Central Role of Conventional Dendritic Cells in Regulation of Bone Marrow Release and Survival of Neutrophils - Jiao, Jingjing (2014)
Neutrophils are the most abundant cell type in the immune system and play an important role in the innate immune response. Using a diverse range of mouse models with either defective DC development or conditional DC depletion, we provide in vivo evidence indicating that conventional dendritic cells (cDC) play an important role in the regulation of neutrophil homeostasis. Flk2, Flt3L and Batf3 knockout mice, which have defects in DC development, have increased numbers of liver neutrophils in the steady state. Conversely, neutrophil frequency is reduced in DC-specific PTEN knockout mice, which have an expansion of CD8+ and CD103+ DCs. In chimeric CD11c-DTR mice, cDC depletion results in a systemic increase of neutrophils in peripheral organs in the absence of histological inflammation or an increase in pro-inflammatory cytokines. This effect is also present in splenectomized chimeric CD11c-DTR mice and is absent in chimeric mice with 50% normal bone marrow. In chimeric CD11c-DTR mice, DT treatment results in enhanced neutrophil trafficking from the bone marrow into circulation and increased neutrophil recruitment. Moreover, there is an increased expression of chemokines/cytokines involved in neutrophil homeostasis and reduced neutrophil apoptosis. These data underscore the role of the DC pool in regulating the neutrophil compartment in non-lymphoid organs.